c.2 - Brahmananda, P. R. (ed.); Panchamukhi, V.R. (ed.) (Bombay, 1987)
The Indian Economy has witnessed three and a half decades of planned economic development. The process has been marked by the emergence of divergent interpretations and controversies, ups and downs, and has generated world-wide interest, for India is the only large democratically developing country which has opted for a mixed economy. On the occasion of the World Economic Congress in December 1986 hosted by India, the Indian Economic Association assigned to the editors the task of marshalling a set of papers by different scholars covering analytically the leading developments in the Indian economy since the fifities. The present volume contains forty two special studies dealing with such diverse topics as growth, distribution, agriculture, industry, infrastructure, trade, money, finance, planning, employment, population and welfare. The authors are all distinguished experts in their different areas of specialisation and together give a vivid account of the Indian economy, which is a veritable laboratory for economists.
Keywords: Indian -Economy